Hierarchies from deterministic non-locality in theory space Anderson localisation - Ketan M. Patel (Journal of High Energy Physics)
Abstract The nearest-neighbour or local mass terms in theory space among quantum fields, with their generic disordered values, are known to lead to the localisation of mass eigenstates, analogous to Anderson localisation in a one-dimensional lattice. This mechanism can be used to create an exponential hierarchy in the coupling between two fields by placing them at opposite ends of the lattice chain. Extending this mechanism, we show that when copies of such fields are appropriately attached to the lattice chain, it leads to the emergence of multiple massless modes. These vanishing masses are a direct consequence of the locality of interactions in theory space. The latter may break down in an ordered and deterministic manner through quantum effects if additional interactions exist among the chain fields. Such non-locality can induce small masses for the otherwise massless modes without necessarily delocalising the mass eigenstates. We provide examples of interactions that preserve or even enhance localisation. Applications to flavour hierarchies, neutrino mass, and the μ-problem in supersymmetric theories are discussed.